DEHP toxicity on vision, neuromuscular junction, and courtship behaviors of Drosophila. (December 2018) - Chen, Mei-Ying; Liu, Hsin-Ping; Liu, Chuan-Hsiu; Cheng, Jack; Chang, Meng-Shiun; Chiang, Su-Yin; Liao, Wing-Ping; Lin, Wei-Yong
Abstract: Bis(2-ethylhexyl) phthalate (DEHP) is the most common plasticizer. Previous studies have shown DEHP treatment accelerates neurological degeneration, suggesting that DEHP may impact retinal sensitivity to light, neurotransmission, and copulation behaviors. Although its neurotoxicity and antifertility properties have been studied, whether DEHP exposure disrupts vision and how DEHP influences neuromuscular junction (NMJ) have not been reported yet. Moreover, the impact of DEHP on insect courtship behavior is still elusive. Fruit flies ( Drosophila melanogaster ) were treated with series concentrations of DEHP and observed for lifespan, motor function, electroretinogram (ERG), electrophysiology of neuromuscular junction (NMJ), courtship behaviors, and relevant gene expression. Our results confirmed the DEHP toxicity on lifespan and capacity of motor function and updated its effect on copulation behaviors. Additionally, we report for the first time that DEHP exposure may harm vision by affecting the synaptic signaling between the photoreceptor and the laminar neurons. Further, DEHP treatment altered both spontaneous and evoked neurotransmission properties. Noteworthy, the effect of DEHP exposure on the copulation behavior is sex-dependent, and we proposed potential mechanisms for future investigation. Graphical abstract: Image 1 Highlights: DEHP exposure may Harm vision by altering retinal sensitivity to the light. Alter both spontaneous and evoked neurotransmission of NMJ. Affect copulation behaviors in a sex-dependent manner.